2019
DOI: 10.3390/ma12162584
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Performance Study of the Sound Absorption of Used Cigarette Butts

Abstract: There has been increasing interest in new sustainable materials that can be used as construction materials. Among them, sound-absorbing materials have an important role in both acoustical room conditioning and in room insulation. As a proposal for recycling, one of the most common residues in the world, cigarette butts, is studied. Samples were prepared with used cigarette butts as acoustical absorbent materials. Several samples were prepared and grouped by similarity. Variability analyses of the samples prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Lastly, analyzing the value of the maximum absorption frequency in Figure 10 reveals that the value clearly shifted when increasing the thickness of the sample. This shift of the maximum absorption frequency with the increasing thickness of the samples has also been described in previous studies and compares well with the shift in other samples (glass wool) showing linear behavior [19,21].…”
Section: Influence Of the Thickness Of The Samplessupporting
confidence: 90%
See 2 more Smart Citations
“…Lastly, analyzing the value of the maximum absorption frequency in Figure 10 reveals that the value clearly shifted when increasing the thickness of the sample. This shift of the maximum absorption frequency with the increasing thickness of the samples has also been described in previous studies and compares well with the shift in other samples (glass wool) showing linear behavior [19,21].…”
Section: Influence Of the Thickness Of The Samplessupporting
confidence: 90%
“…In previous studies related to the use of cigarette butts for making acoustic absorbing materials, the absorption of samples prepared with cigarette butts was quite satisfactory and found to be comparable to or even better than other materials conventionally used for absorption [17][18][19][20]. In the present study, we aimed to perform an in-depth investigation of the use of used cigarette butts for obtaining acoustic absorbing materials.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…As a new proposal for recycling this waste, over the past few years our research group has been working on the elaboration of an acoustical absorber material obtained from used cigarette butts. In these studies [ 20 , 21 , 22 , 23 ], absorption of the prepared samples (some of them desegregating the cigarette butt filters, but mainly manually inserting them) was fairly satisfactory, being comparable to or even better than those of some other materials conventionally used for sound absorption.…”
Section: Introductionmentioning
confidence: 99%
“…A second group of papers focused its attention on the use of natural or recycled components to create a skeleton of porous materials with sound-absorbing purposes. Cigarette butts of different lengths and under different conditions (smoked or non-smoked) were used by Gómez Escobar et al [ 6 ] to produce small samples that were tested in a standing wave tube. The results showed that acceptable sound absorption could be obtained from about 2 kHz on, with small variations depending on the butts’ length and smoking conditions.…”
mentioning
confidence: 99%